Sociological Perspective in Handling Conflicts in Public Health Issues - Ruagadi, Henry A.; Bunga, Nurfhin Ilma; Pelima, Joice Noviana; Yakobus, I Ketut; Nursinah, A. (International Journal of Health Sciences, 2025)
This study aims to identify the social factors that cause inequality in access to health services in the community and analyze the dynamics of interaction between medical personnel and patients that contribute to conflicts in the health sector. This study uses a qualitative approach with a case study method, involving in-depth interviews with five informants consisting of patients, medical personnel, and health facility managers. The results showed that socioeconomic inequality, educational level, geographical conditions, and uneven health policies are the main factors causing inequality in access to health services. In addition, ineffective communication dynamics, different expectations, and power imbalances between medical personnel and patients contribute significantly to conflicts in medical interactions. This study suggests the need for improvements in the distribution of health resources, increased public health literacy, and communication training for medical personnel to reduce inequality and prevent conflict. These findings are expected to provide insights for the development of more inclusive health policies and improve the relationship between medical personnel and patients.